Analyzing Collaborative Governance in Tourism Development: A Case Study of Karampuang Island, West Sulawesi - Idris, Muhammad; Anwar, Yusuf; Syukur, Alam Tauhid; Mustamin, Nur Afifah (Jurnal Borneo Administrator, 2025)
Tourism is a strategic sector for regional development; however, the management of flagship destinations in developing regions frequently encounters challenges related to weak stakeholder coordination, limited infrastructure, and insufficient community participation. Karampuang Island in West Sulawesi possesses significant natural and cultural tourism potential, yet its development has not been optimally managed due to low inter-agency synergy and limited stakeholder engagement. This study aims to analyze the implementation of the pentahelix collaborative governance model, comprising government, private sector, academia, community or non-governmental organizations, and media, in the development of Karampuang Island as a tourism destination. A qualitative descriptive approach was employed, using in-depth interviews, field observations, and document analysis. The findings indicate that cross-sector collaboration has contributed to improvements in accessibility and public facilities, as reflected in the construction of Plaza Karampuang and the establishment of twelve micro, small, and medium enterprise kiosks. Nevertheless, formal coordination mechanisms remain weak due to the absence of inter-agency memorandums of understanding, limiting sustained collaboration. Private sector involvement in promotion and investment is still minimal, while academic contributions are largely confined to community service programs. Community participation has increased through the Tourism Awareness Group, although communication with government actors remains suboptimal. Media actors have actively promoted the destination, yet digital marketing strategies have not been maximized. In conclusion, the pentahelix model has the potential to strengthen tourism governance on Karampuang Island, provided it is supported by formal coordination platforms, community capacity building, and integrated digital marketing strategies to ensure sustainable tourism development and local community welfare.